Industrial designs and models under Algerian Law: Legal protection and economic exploitation as intellectual property assets - Yamina, Houichi (The International tax journal, 2026)
Industrial designs and models are subject to the same legal rules, both with regard to the conditions required for their protection and the legal effects arising from such protection at both the national and international levels. Industrial property rights occupy an intermediate position between pure art and applied or industrial art. Industrial property and literary and artistic property are connected through the principle of the unity of art; consequently, industrial designs and models may also be protected under copyright and related rights legislation, particularly Ordinance No. 03-05. Industrial designs and models are entitled to criminal protection only after the completion of the procedures of filing, registration, and publication in accordance with the applicable legislative and regulatory provisions. The definition of industrial designs and models adopted by the Algerian legislator has been overtaken by developments, as it originates from an old law enacted nearly sixty years ago. During this period, legislation has undergone significant reforms that elevated industrial designs and models to the rank of fundamental industrial property rights, particularly with regard to registration procedures and the strengthening of legal protection.